Analysis of the Application of Business Ethics in Making Decisions in the Era of Globalization - Mentari Purba; Purba, Bonaraja (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is the basis for finding out how to apply ethics in the practice of economic decision making in order to manage a company as fairly as possible and comply with applicable laws. Therefore, based on the results and discussion of this research, it can be concluded that in making business ethics decisions, the social, environmental and economic consequences of the various decisions and actions that will be taken will be taken into account. In this context, the magazine shows that technology, when used wisely, can be a tool for improving the application of business ethics. Companies can use technology to increase transparency, accountability and data security. However, we must understand deeply that technology can also be a source of abuse if it is not properly monitored. Overall, this magazine emphasizes the importance of practicing business ethics in the era of digitalization. The implication of this analysis is that business success in the digital era does not only depend on technological innovation, but also the extent to which ethical values are applied to all aspects of the company's operations and its interactions with consumers, society and others